Welding and joining of aerospace materials - Chaturvedi, M. C. (Woodhead Publishing in materials., 2012)
Welding and joining techniques play an essential role in both the manufacture and in-service repair of aerospace structures and components, and these techniques become more advanced as new, complex materials are developed. Welding and joining of aerospace materials provides an in-depth review of different techniques for joining metallic and non-metallic aerospace materials. Part one opens with a chapter on recently developed welding techniques for aerospace materials. The next few chapters focus on different types of welding such as inertia friction, laser and hybrid laser-arc welding. The final chapter in part one discusses the important issue of heat affected zone cracking in welded superalloys. Part two covers other joining techniques, including chapters on riveting, composite-to-metal bonding, diffusion bonding and recent improvements in bonding metals. Part two concludes with a chapter focusing on the use of high-temperature brazing in aerospace engineering. Finally, an appendix to the book covers the important issue of linear friction welding. With its distinguished editor and international team of contributors, Welding and joining of aerospace materials is an essential reference for engineers and designers in the aerospace, materials and welding and joining industries, as well as companies and other organisations operating in these sectors and all those with an academic research interest in the subject. Provides an in-depth review of different techniques for joining metallic and non-metallic aerospace materialsDiscusses the important issue of heat affected zone cracking in welded superalloysCovers many joining techniques, including riveting, composite-to-metal bonding and diffusion bonding.